PENGARUH MEDIA FLASHCARD BERBASIS METODE GLOBAL TERHADAP KETERAMPILAN MEMBACA KATA SISWA KELAS II SD - Aulia, Dinar; Bahauddin Azmy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of flashcard media based on the Global Method on the word reading skills of second-grade elementary school students. The study was motivated by students’ low word reading ability, particularly in terms of fluency, accuracy, and holistic word recognition. A quantitative approach was employed using a quasi-experimental design with a Nonequivalent Control Group Design. The participants consisted of 46 second-grade students divided into an experimental group and a control group. Data were collected through pre-test and post-test instruments measuring word reading skills. The data were analyzed using normality and homogeneity tests followed by an Independent Samples t-test. The findings revealed that the post-test mean score of the experimental group (88.48) was higher than that of the control group (75.96). the hypothesis testing showed a significance value of 0.000 (< 0.05), indicating a statistically significant effect. Therefore, flashcard media based on the Global Method significantly improves students’ word reading skills, particularly in terms of fluency and accuracy.